2010
DOI: 10.1002/pssa.201026309
|View full text |Cite
|
Sign up to set email alerts
|

Reverse biased electroluminescence spectroscopy of crystalline silicon solar cells with high spatial resolution

Abstract: Electroluminescence spectra of different types of crystalline silicon solar cells obtained under reverse bias are analysed on a macroscopic as well as on a microscopic scale. The calibrated spectra of all samples exhibit a dominant peak at the band-gap energy E g % 1.1 eV. Although the fraction of visible light may vary over one order of magnitude, the shapes of the calibrated spectra are qualitatively similar. Single emission sites have been investigated with respect to the externally applied voltage V and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 20 publications
1
18
1
Order By: Relevance
“…2 This part of the spectrum makes ReBEL visible to the naked eye. Recent calibrated measurements of ReBEL in multi-crystalline silicon solar cells 22 demonstrated a spectral behaviour very similar to those earlier results. Reference 22 also showed the presence of an emission peak around the band gap energy of silicon and, additionally, demonstrated that the size of the individual emitting centres is well below the resolution limit of an optical microscope.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…2 This part of the spectrum makes ReBEL visible to the naked eye. Recent calibrated measurements of ReBEL in multi-crystalline silicon solar cells 22 demonstrated a spectral behaviour very similar to those earlier results. Reference 22 also showed the presence of an emission peak around the band gap energy of silicon and, additionally, demonstrated that the size of the individual emitting centres is well below the resolution limit of an optical microscope.…”
supporting
confidence: 86%
“…However, this dependence is masked by the series resistance in the emitter and the base of the solar cell. 22,23 While the research for the causes of the defect emission under reverse bias reached a satisfactory status with the characterisation of the three types, 10 there is no clear understanding of the light generation process. A key to find a proper model of the processes happening is a reliable ReBEL spectrum.…”
mentioning
confidence: 99%
“…This problem has recently been solved on alkaline-etched solar cells by applying bias-dependent high spatial resolution ReBEL investigations. 32 Note that in these cells the onset voltages are higher than in the acid-etched cells shown until now, see Ref. 13.…”
Section: B Defect-induced Breakdownmentioning
confidence: 70%
“…Moreover, it cannot be excluded that a−FeSi 2 is not the only type of precipitates leading to type−2 breakdown sites. It was shown by Schne− emann et al [61] that indeed the onset voltages of different type−2 breakdown sites are different, and that the current through each site is series resistance−limited. Only the su− perposition of an ensemble of many breakdown sites with consecutive appearance of breakdown currents leads to the exponentially increasing reverse current observed for the whole cell.…”
Section: The Reverse Currentmentioning
confidence: 99%